PERAN BOTOH DALAM MEMPENGARUHI PERILAKU PEMILIH PADA PEMILIHAN KEPALA DESA DI DESA WATES KABUPATEN KEDIRI TAHUN 2019 - Novitasari, Indah; Mali, Fransiskus X. Gian Tue (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
The election of village heads is an implementation of democratization at the local level within the framework of village autonomy. The legal basis for the implementation of this village head election is the Village Law Number 6 of 2014. However, the phenomenon of gamblers, or botoh in Javanese, has also made the general election arena a gambling arena. Several studies have shown that botohs become vote buyers, donors, success teams, or just simply gambling. So that in these various roles, botoh is able to influence voter choices so that the candidate he chooses wins the general election, and botoh wins gambling. This study aims to find and describe the role of botoh in the election of the village head of Wates, Kediri Regency in 2019. The research method used was interviews and observations conducted before the election of the village head, and on the election day of the village head of Wates. The research approach used is a qualitative approach, with an exploratory descriptive type of research. The results showed that botoh in the 2019 Wates village head election consolidated and influenced voters during the campaign period until election day. Consolidation is carried out by collecting data, convincing, strengthening beliefs, paying for a number of materials, and providing accommodation during election day. So that botoh becomes a threat to the procedural democratic process in Indonesia, it needs to be eliminated by sharing procedural, legal, and political approaches.